When lunch fights back : wickedly clever animal defenses - Johnson, Rebecca L. (Millbrook Press, 2015)
Presents the various types of defenses mechanisms used by animals, including the bone spikes of the African hairy frog, the deadly poison of the blue-spotted N. taracua termite, and the hammer-like punch of the peacock mantis shrimp.